Bioresorbable scaffold: Never say never. Issue 2 (7th February 2020) - Musumeci, Giuseppe; Baralis, Giorgio
Key Points: Bioresorbable vascular scaffolds (BVSs) were designed to overcome the limitations of metallic stents. Absorb BVS has provided information about strut thickness, scaffold degradation, vessel wall coverage, and their influence on thrombosis. Clinical trials have shown higher rates of target vessel myocardial infarction and stent thrombosis with the absorb BVS than with second‐generation drug‐eluting stents.